1961
DOI: 10.1590/s0006-87051961000100048
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento do estado nutricional de pomares cítricos de São Paulo pela análise foliar

Abstract: O trabalho relata o estudo da composição em nutrientes das folhas de laranjeiras de 40 pomares localizados em diferentes zonas citrícolas do Estado de São Paulo, com a finalidade de obter elementos quanto ao índice geral de nutrição, nas diversas áreas de produção. Simultaneamente com as amostras de fôlhas, foram colhidas observações quanto, ao tipo de solo, adubação, variedade, porta-enxêrto, produção, pulverizações, aspecto (vigor, sintomas de desnutrição, moléstias etc.). Amostras de solo de cada pomar fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

1970
1970
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…In other studies, leaf K content of 1.0-1.7% has been suggested as optimum K concentration and 0.87% as critical level in 6-7-month-old leaves from fruit-bearing terminals of 'Valencia' orange (Rodriguez and Gallo 1961 ) . In South Africa, critical limit of leaf K was observed as 0.9% in 7-9-month-old leaves from fruits bearing terminals and leaf K content of 0.55-0.80% associated with a N/K ratio of 3.3-4.1 for maximum production and fruit size of Valencia' orange in Citrusdal area (Du Plessis 1977 ).…”
Section: Critical Nutrient Conceptmentioning
confidence: 89%
See 1 more Smart Citation
“…In other studies, leaf K content of 1.0-1.7% has been suggested as optimum K concentration and 0.87% as critical level in 6-7-month-old leaves from fruit-bearing terminals of 'Valencia' orange (Rodriguez and Gallo 1961 ) . In South Africa, critical limit of leaf K was observed as 0.9% in 7-9-month-old leaves from fruits bearing terminals and leaf K content of 0.55-0.80% associated with a N/K ratio of 3.3-4.1 for maximum production and fruit size of Valencia' orange in Citrusdal area (Du Plessis 1977 ).…”
Section: Critical Nutrient Conceptmentioning
confidence: 89%
“…While Ishihara et al ( 1972 ) suggested critical limit based on various plant organs and accordingly, critical limit of Cu was found as 4.0, 3.0, 3.8, and 10.0 ppm for leaves, shoots, fruits, and fi ne roots, respectively. Rodriguez and Gallo ( 1961 ) observed the critical level of N, P, K, Ca, and Mg as 2.20%, 0.12%, 1.00%, 3.00%, and 0.30%, respectively. Coetzee ( 1980 ) suggested critical limit of K as 0.70-0.80% for Valencia orange.…”
Section: Critical Nutrient Conceptmentioning
confidence: 90%
“…Esse tipo de trabalho já foi desenvolvido em São Paulo e trouxe importante contribuição para identificar a situação nutricional de culturas como a do café (GALLO et ai., 1970), citros (RODRIGUEZ & GALLO, 1961) e banana (GALLO et ai., 1974). A partir desse conhecimento, delimitaram-se áreas com problemas nutricionais específicos, contribuindo para a indicação de experimentos para essas regiões.…”
Section: Introductionunclassified
“…(1960), onde foram analisadas folhas de laranjeira Baianinha. RODRIGUEZ & GALLO (1961) e CAETANO et al (1984, também no Brasil, não encontraram correlação entre a análise do solo e de folhas de citros. O mesmo ocorreu com ANDERSON & ALBRIGO (1971) nos EUA.…”
Section: Avaliação Da Fertilidade Do Solo E Do Estado Nutricional Na unclassified